2021
DOI: 10.1038/s42003-021-02310-y
|View full text |Cite
|
Sign up to set email alerts
|

SCD2-mediated monounsaturated fatty acid metabolism regulates cGAS-STING-dependent type I IFN responses in CD4+ T cells

Abstract: Host lipid metabolism and viral responses are intimately connected. However, the process by which the acquired immune systems adapts lipid metabolism to meet demands, and whether or not the metabolic rewiring confers a selective advantage to host immunity, remains unclear. Here we show that viral infection attenuates the expression of genes related to lipid metabolism in murine CD4+ T cells, which in turn increases the expression of antiviral genes. Inhibition of the fatty acid synthesis pathway substantially … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…In addition, TBK1 and IRF3 activation, both downstream effectors of STING, also regulate central metabolic pathways ( Kumari et al., 2016 ; Zhao et al., 2018 ), including fatty acid metabolism ( Tang et al., 2021 ). Conversely, fatty acid biosynthesis pathways have been proposed to participate in controlling antiviral responses through modulation of the expression of interferon-stimulated genes (Isg) ( Kanno et al., 2021 ). While these studies highlight a role of STING activation and ensuing activation of downstream effectors in the maintenance of metabolic homeostasis, there is as of today no indication of a direct role of STING in metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TBK1 and IRF3 activation, both downstream effectors of STING, also regulate central metabolic pathways ( Kumari et al., 2016 ; Zhao et al., 2018 ), including fatty acid metabolism ( Tang et al., 2021 ). Conversely, fatty acid biosynthesis pathways have been proposed to participate in controlling antiviral responses through modulation of the expression of interferon-stimulated genes (Isg) ( Kanno et al., 2021 ). While these studies highlight a role of STING activation and ensuing activation of downstream effectors in the maintenance of metabolic homeostasis, there is as of today no indication of a direct role of STING in metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Our data further indicated that selective decrease in monounsaturated fatty acid (MUFA) biosynthesis is crucial for the induction of type I-IFN response in CD4 + T cells ( 18 ). Indeed, CRISPR/Cas9-mediated genome editing of the stearyl-CoA desaturase 2 (Scd2), which is responsible for MUFA biosynthesis, dramatically increased the expression of ISGs in CD4 + T cells ( 18 ). On the other hand, type I-IFN signaling changes the fatty acid oxidization, OXPHOS and expression levels of genes related to lipid metabolism in pDCs and macrophages ( 19 ).…”
Section: Introductionmentioning
confidence: 52%
“…Bensinger et al showed that altering the balance between cholesterol biosynthesis and scavenging, rather than reducing the endogenous lipid pool size, is essential for achieving type I-IFN responses in macrophage ( 17 ). We also previously found that genetic deletion or pharmacological inhibition of acetyl-CoA carboxylase (ACC1), which is rate limiting enzyme of fatty acid biosynthesis, substantially increases the basal expression of ISGs via the spontaneous production of type I-IFN ( 18 ). Our data further indicated that selective decrease in monounsaturated fatty acid (MUFA) biosynthesis is crucial for the induction of type I-IFN response in CD4 + T cells ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of several IFN-related cytokines, including IRF3, IRF7 and ISG15, as well as that of proinflammatory cytokines, such as IL-6, IL-8 and TNFα, were all significantly increased. Increased research has demonstrated that inhibition of the fatty acid synthesis pathway substantially increases the basal expression of antiviral genes via the spontaneous production of type I interferons (IFN) [39]. The lack of ω-3 FAs could disturb lipid metabolism homeostasis and thus induced proinflammation metabolites synthesis [40].…”
Section: Discussionmentioning
confidence: 99%